Corporate social responsibility through an economic lens - Robert N. Stavins; Forest L. Reinhardt; Richard H. K. Vietor (Fondazione Eni Enrico Mattei (FEEM), 2008)
Business leaders, government officials, and academics are focusing considerable attention on the concept of corporate social responsibility (CSR), particularly in the realm of environmental protection. Beyond complete compliance with environmental regulations, do firms have additional moral or social responsibilities to commit resources to environmental protection? How should we think about the notion of firms sacrificing profits in the social interest? May they do so within the scope of their fiduciary responsibilities to their shareholders? Can they do so on a sustainable basis, or will the forces of a competitive marketplace render such efforts and their impacts transient at best? Do firms, in fact, frequently or at least sometimes behave this way, reducing their earnings by voluntarily engaging in environmental stewardship? And finally, should firms carry out such profit-sacrificing activities (i.e., is this an efficient use of social resources)? We address these questions through the lens of economics, including insights from legal analysis and business scholarship.
Keywords: M14; L51; Q50; 330; Corporate Social Responsibility; Voluntary Environmental Performance